IMPLEMENTASI PENDIDIKAN AKHLAK DALAM MEMBENTUK KARAKTER SANTRI DIPONDOK PESANTREN IMAM AL-BUKHARI FIRDAUS - Ainul Husna; Mukarom Mukarom (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
The moral decline of the younger generation is a major challenge for Islamic educational institutions today. This study aims to explain the implementation of moral education at the Imam Al-Bukhari Firdaus Islamic Boarding School in an effort to shape the noble character of its students. Using qualitative methods with a phenomenological approach, this study explores the direct experiences of the subjects through stages of observation, in-depth interviews, and documentation studies. Data analysis was carried out through data reduction, presentation, and drawing conclusions to obtain a holistic understanding. The results show that moral education is implemented as an integrated value system in all daily activities of the students, not just a formal class program. This implementation is carried out through routine habits, continuous supervision, and real examples from teachers who are determining factors for success. The use of the classic book Washoya Al-Aba' Lil Abna' provides concrete guidance in developing adab (good manners) towards Allah, teachers, and fellow human beings. The findings reveal a significant increase in the students' discipline, politeness, and social responsibility through a dynamic process of internalization of values. The main conclusion confirms that the character of students is formed naturally through a religious environment that consistently prioritizes adab (good manners) above knowledge. Moral education at this Islamic boarding school has succeeded in becoming a spiritual foundation that equips students to contribute positively to the lives of the wider community while also becoming a strong moral fortress in facing the increasingly challenging currents of globalization for future generations. ABSTRAK Kemerosotan moral generasi muda menjadi tantangan besar bagi lembaga pendidikan Islam saat ini. Penelitian ini bertujuan untuk menjelaskan implementasi pendidikan akhlak di Pondok Pesantren Imam Al-Bukhari Firdaus dalam upaya membentuk karakter mulia para santri. Menggunakan metode kualitatif dengan pendekatan fenomenologi, penelitian ini menggali pengalaman langsung para subjek melalui tahapan observasi, wawancara mendalam, serta studi dokumentasi. Analisis data dilakukan melalui reduksi, penyajian, dan penarikan simpulan guna memperoleh pemahaman holistik. Hasil penelitian menunjukkan bahwa pendidikan akhlak dilaksanakan sebagai sistem nilai terintegrasi dalam seluruh aktivitas keseharian santri, bukan sekadar program formal kelas. Implementasi tersebut dilakukan melalui pembiasaan rutin, pengawasan berkelanjutan, serta keteladanan nyata dari para pengajar yang menjadi faktor penentu keberhasilan. Penggunaan kitab klasik Washoya Al-Aba’ Lil Abna’ memberikan panduan konkret dalam membangun adab terhadap Allah, guru, dan sesama manusia. Temuan mengungkapkan adanya peningkatan signifikan pada kedisiplinan, kesopanan, dan tanggung jawab sosial santri melalui proses internalisasi nilai yang dinamis. Simpulan utama menegaskan bahwa karakter santri terbentuk secara alami melalui lingkungan religius yang konsisten mengedepankan adab di atas ilmu. Pendidikan akhlak di pesantren ini berhasil menjadi fondasi spiritual yang membekali santri untuk berkontribusi positif dalam kehidupan masyarakat luas sekaligus menjadi benteng moral yang kuat menghadapi arus globalisasi yang kian menantang bagi generasi masa depan.